Difference Disease Knowledge Level in Type 2 Diabetes Mellitus Patients at Siloam Lippo Village General Hospital - Moningkey, Shirley Ivonne; Aprilyanri, Iegreat; Atmodjo, Wahyuni Lukita (Medicinus, 2024)
Background: In Indonesia, Diabetes Mellitus (DM) with complications is the third leading cause of death. Risk of complication increases tremendously in uncontrolled diabetes. The level of knowledge is one of the factors affect glycaemic control. However, little study has been done regarding the difference in disease knowledge level in type 2 DM patients. This study aims to find out the difference between the level of DM knowledge and glycaemic control in type 2 diabetes mellitus patients at Siloam Lippo Village General Hospital.Methods: Analytical observational with a cross-sectional study was conducted. 46 type 2 diabetes mellitus patients qualified for the inclusion criteria and were given the self-administered Michigan Diabetes Knowledge Test (MDKT) for General Knowledge Part (GKP) questionnaire and HbA1c test results taken in the past six months to evaluate glycaemic control. Purposive sampling method was used in this study for data collection. Student T-test was done to measure the difference with 95% significancy.Result: In 46 samples were shown that 60.90% women, a majority in the 50-59 age group, and 65.20% with more than 5 years of DM history. Among 46 samples, 26 have uncontrolled glycaemic with a mean score of 6.65 ± 1.83 in knowledge, and 20 have controlled glycaemic with a mean score 7.80 ± 1.61. Student T-test showed significant difference in level of knowledge between controlled and uncontrolled glycaemic levels with p = 0.032.Conclusions: It is concluded that there is a difference in disease knowledge level in type 2 DM patients at Siloam Lippo Village General Hospital.